Understanding the Notion “Marriage” in British Lingvoculture (By Means of its Verbalization) - Pupynina, Elena V.; Pugach, Vladimir S.; Smirnova, Stanislava B.; Kuchmistyy, Vladislav A.; Yatsenko, Yulia N. (Journal of History Culture and Art Research, 2017)
The article deals with the studying the structure of the subconcept «marriage» in modern British lingvoculture. The subconcept is viewed as one of the basic conceptual structural elements of the concepts sphere “family relations’. The study of the language filling is taken by means of lexicographic description of the lexemes possessing the corresponding to the attractors denotational meaning and studying the literature in the aspect of using the connotational meaning to show the peripheric field. When the linguistic study is done then the subconcept is structurised so that the internal structural features could be viewed and then it could be studied on the aspect of reflecting the social changes of the family phenomenon in the society and find out which changes are reflected in the language. The study resulted in the changes of the traditional structure caused by the social changes. These are the lack of traditional ceremonies resulted in the simplifying of the wedlock, appearing multiple marriages, as well as partners instead of spouses.